Quantification of natural parasitism by Braconidae and Ichneumonidae (Hymenoptera) in larvae of the corn earworm (Spodoptera frugiperda Smith) in Santa Cruz, Guanacaste - Mora-Prendas, Jairo (2025)
Spodoptera frugiperda populations are naturally regulated by natural enemies such as parasitoids and predators. Despite this, the lack of knowledge about these ecological groups and the heavy reliance on synthetic insecticides in production systems drastically reduce beneficial entomofauna. To understand the complex of parasitoids associated with S. frugiperda, as well as their richness and abundance at the Finca Experimental de Santa Cruz, biweekly collections of immature stages of the pest were conducted in 2021. The larvae were reared in the laboratory until they completed their biological cycle or parasitoids emerged. A total of 233 parasitized larvae were recorded, classified into four species of parasitoids, which exerted a regulation of 38.77%. The reported species were: Chelonus insularis, Chelonus cautus, Archytas sp., and Pristomerus spinator. It is concluded that the pest shows significant regulation at the FESC. However, it is recommended to increase the study locations to better understand the distribution and faunal composition of S. frugiperda parasitoids in Guanacaste.